2019
DOI: 10.1109/access.2019.2893283
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Controller Placement Problem in Software-Defined Networking

Abstract: In order to simplify the management of the traditional network, software-defined networking (SDN) has been proposed as a promising paradigm shift that decouples control plane and data plane, providing programmability to configure the network. With the deployment and the applications of SDN, researchers have found that the controller placement directly affects network performance in SDN. In this paper, the state of the art of controller placement problem is surveyed from the perspective of optimization objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 55 publications
0
95
0
Order By: Relevance
“…The controller selection based on shortest distance between the nodes is not the right choice to optimize the load and robustness of the network. It is found that the path latency‐based selection of number of controllers build a robust network . Optimal number of controllers are needed to improve the network performance.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The controller selection based on shortest distance between the nodes is not the right choice to optimize the load and robustness of the network. It is found that the path latency‐based selection of number of controllers build a robust network . Optimal number of controllers are needed to improve the network performance.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In an attempt to address these questions, several selection algorithms have been presented with one or multiple objective functions: lowering network delay, improving network resilience, or a combination of thereof …”
Section: Background and Related Workmentioning
confidence: 99%
“…In an attempt to address these questions, several selection algorithms have been presented with one or multiple objective functions: lowering network delay, improving network resilience, or a combination of thereof. [36][37][38] Heller et al introduced two selection algorithms using k-median and k-center metrics. The k-median algorithm selects controllers to minimize the minimum average shortest path lengths between SDN switches and controllers.…”
Section: Controller Placement Problemmentioning
confidence: 99%
“…Second, the SDN Controller coverage should be defined carefully taking into account the density and mobility of vehicles. This helps avoiding SDN controllers' overload as well as improving the performance of vehicle-to-controller communications, and also, minimizing the number of changes in the set of deployed controllers.Even if the SDN controller placement problem has been widely covered in the literature, as described in References [13,14], most existing work focused on wired networks and aimed at computing an off-line optimal placement. In this paper, as in Reference [15], the focus is on controller placement in a SDVN context.…”
mentioning
confidence: 99%
“…Even if the SDN controller placement problem has been widely covered in the literature, as described in References [13,14], most existing work focused on wired networks and aimed at computing an off-line optimal placement. In this paper, as in Reference [15], the focus is on controller placement in a SDVN context.…”
mentioning
confidence: 99%